Diversity of arbuscular mycorrhizal fungi in alkaline soils of hot sub humid eco-region of Middle Gangetic Plains of India. (4th July 2019) - Parihar, Manoj; Rakshit, Amitava; Singh, Harikesh Bahadur; Rana, Kiran
ABSTRACT: The aim of this study was to evaluate the diversity and distribution of arbuscular mycorrhizal (AM) fungi in the salt affected soils of Varanasi district. Saccharum munja Roxb. was predominate among all the vegetation and shown strong AM fungal colonisation. Soil characteristics revealed their neutral to alkali nature and habituated six genera and eight different species of AM fungi i.e. Acaulospora (1), Cetraspora (1), Entrophospora (1), Funneliformis (2- F. geosporum and F. mosseae ), Glomus (1), Rhizolglomus (2- R. intraradices and R. fasciculatum ) in the rhizosphere of native salt tolerant vegetation. Rhizolglomus fasciculatum was the most widely distributed species under strongly alkaline condition (52.96%) while Funneliformis mosseae was well distributed under slightly (22.99%) to moderately alkaline condition (35.78%). Soil alkalinity was observed to be detrimental for AMF but members of family Glomeraceae registered their presence more frequently (∼65%) with higher spore density showing strong adaptation which might be helpful in restoration of moderately to strongly alkaline disturbed eco-region.